Antagonistic trait of Staphylococcus succinus strain AAS2 against uropathogens and assessment of its in vitro probiotic characteristics. (May 2018) - Khusro, Ameer; Aarti, Chirom; Salem, Abdelfattah Z.M.; Buendía Rodríguez, German; Rivas-Cáceres, Raymundo Rene
Abstract: The desideratum aim of the present context was to isolate a promising antagonist probiotic bacterium from fermented food item as biocontrol agent against uropathogens. Among diversified isolates evaluated for antagonistic trait, Staphylococcus succinus strain AAS2 was found to be an auspicious candidate against urinary tract infection (UTI) causing bacterial pathogens, being the most active against Staphylococcus aureus with substantial activity of 352.5 ± 5.4 AU/mL. Further, the in vitro probiotic attributes of strain AAS2 were assessed using systematic methodology. The isolate exhibited tolerance to acidic condition (up to pH 3.0) and simulated gastric juice (at pH 3.0) with fairly high survival logarithmic cell counts of 5.3 ± 0.15 and 5.23 ± 0.02 log cfu/mL, respectively. Additionally, strain AAS2 showed capability to resist 0.5% w/v bile salt too. It also revealed significant values of auto-aggregation (32.5 ± 1.3–56.5 ± 1.4%) and cell surface hydrophobicity (38.35 ± 1.4%) properties. The isolate showed resistivity towards phenol (6.8 ± 0.08 log cfu/mL) and lysozyme (58.6 ± 1.6%). Further, the susceptibility trait of strain AAS2 to conventional antibiotics made this isolate a promising probiotic bacterium. Most importantly, the isolate depicted DPPH (2, 2-Diphenyl-1-picrylhydrazyl) and hydroxyl radical scavenging activities in a concentration dependent manner, thereby exhibiting its propitious antioxidative properties. In a nutshell, the outcomes of this investigation divulge the plausible use of S. succinus strain AAS2 as biocontrol agent against uropathogens, and recommended further applications in pharmaceutics due to its pronounced probiotic traits. Highlights: S. succinus strain AAS2 showed pronounced activity against S. aureus. Strain AAS2 showed viability towards low pH, simulated gastric juice, and oxgall. Strain AAS2 exhibited resistance to phenol and lysozyme. Susceptibility of isolate to all tested antibiotics was observed. Propitious DPPH and hydroxyl radical scavenging properties were estimated.